Bandung Cooperation with Braunschweig (Germany) in Realizing Smart City - BJ Tina Rosaliana; Dyah Estu Kurniawati; Deva Joshua Kamisi (Journal of Paradiplomacy and City Networks, 2022)
The Bandung City has carried out various international cooperations to obtain investments in the long or short term, support for infrastructure development, youth exchanges, cooperation in culture, and receipt of fees and grant funds. One of the various cooperations is the efforts of Bandung in paradiplomacy through the sister city concept. This study is necessary because Bandung and Braunschweig have carried out the Sister City Program from 1960 to 2021. This research is a descriptive study with a qualitative approach, examining why Bandung maintains cooperation with Braunschweig (Germany), running for more than 40 years. This article employed data collected from journals, news in the mass media, and information from the official websites of related parties as supporting references. In answering the research question, the author utilized the concepts of smart city and sister city. This study discovered that Bandung maintained its cooperation with Braunschweig due to its interest in building a smart city.